Effects of the combination of red dragon fruit, kiwi, and young coconut water on blood pressure through ACE inhibition and antioxidant mechanisms in pre-elderly women: A quasi-experimental study - Afifah Rifda; Tonny Cortis Maigoda; Okdi Natan; Arie Krisnasary; Jumiyati Jumiyati (AcTion: Aceh Nutrition Journal, 2026)
Hypertension is a major health concern among pre-elderly women, particularly those aged ≥45 years, as the hormonal changes associated with menopause exacerbate susceptibility. This study aimed to evaluate the effects of combined red dragon fruit (Hylocereus polyrhizus), green kiwi (Actinidia deliciosa), and young coconut water (Cocos nucifera) juice on blood pressure among women aged 45–59 years with prehypertension at the Sawah Lebar Primary Health Center in Bengkulu. A quasi-experimental pretest–posttest design was used with 30 participants in this study. Participants were assigned to the intervention (n=15; 230 mL juice twice daily for 7 days combined with exercise and nutrition counseling) or control (n = 15; counseling only) groups. Blood pressure was measured at baseline and post-intervention. Statistical analyses were performed using paired and independent t-tests (p<0.05) and ANCOVA. The intervention group showed a significant reduction in systolic (137.0±1.81 to 122.47±2.32 mmHg) and diastolic pressures (87.07±1.43 to 81.87±1.50 mmHg) compared with the control group (systolic: 135.87±2.29 to 132.40±2.77 mmHg; diastolic: 87.27±1.22 to 84.87±1.55 mmHg). The high potassium content (1,041.5 mg/serving) may enhance vasodilation, inhibit angiotensin-converting enzyme activity, and reduce sodium retention. Confounders (BMI, sodium intake, and physical activity) contributed <25% of the variance. This functional juice effectively reduced blood pressure, supporting its role in non-pharmacological strategies for hypertension management. Larger and longer trials are required to confirm the long-term benefits.